Design, synthesis and antibacterial evaluation of honokiol derivatives. Issue 4 (15th February 2018) - Wu, Bo; Fu, Su-hong; Tang, Huan; Chen, Kai; Zhang, Qiang; Peng, Ai-Hua; Ye, Hao-Yu; Cheng, Xing-Jun; Lian, Mao; Wang, Zhen-ling; Chen, Li-Juan
Graphical abstract: Highlights: 12 novel honokiol derivatives were evaluated for antibacterial activity in vitro . 7c exhibited excellent broad spectrum antibacterial efficiency in vitro . 7c displayed faster bactericidal kinetics against S. aureus than positive control. Abstract: Staphylococcus aureus is a major and dangerous human pathogen that causes a range of clinical manifestations of varying severity, and is the most commonly isolated pathogen in the setting of skin and soft tissue infections, pneumonia, suppurative arthritis, endovascular infections, foreign-body associated infections, septicemia, osteomyelitis, and toxic shocksyndrome. Honokiol, a pharmacologically active natural compound derived from the bark of Magnolia officinalis, has antibacterial activity against Staphylococcus aureus which provides a great inspiration for the discovery of potential antibacterial agents. Herein, honokiol derivatives were designed, synthesized and evaluated for their antibacterial activity by determining the minimum inhibitory concentration (MIC) against S. aureus ATCC25923 and Escherichia coli ATCC25922 in vitro . 7c exhibited better antibacterial activity than other derivatives and honokiol. The structure-activity relationships indicated piperidine ring with amino group is helpful to improve antibacterial activity. Further more, 7c showed broad spectrum antibacterial efficiency against various bacterial strains including eleven gram-positive and seven gram-negative species. Time-kill kinetics against S. aureus ATCC25923 in vitro revealed that 7c displayed a concentration-dependent effect and more rapid bactericidal kinetics better than linezolid and vancomycin with the same concentration. Gram staining assays of S. aureus ATCC25923 suggested that 7c could destroy the cell walls of bacteria at 1 × MIC and 4 × MIC.